Treatment of Antibody-Mediated Renal Allograft Rejection: Improving Step by Step. (31st January 2017) - Lachmann, Nils; Duerr, Michael; Schönemann, Constanze; Pruß, Axel; Budde, Klemens; Waiser, Johannes
Abstract : Throughout the past years we stepwise modified our immunosuppressive treatment regimen for patients with antibody-mediated rejection (ABMR). Here, we describe three consecutive groups treated with different regimens. From 2005 until 2008, we treated all patients with biopsy-proven ABMR with rituximab (500 mg), low-dose (30 g) intravenous immunoglobulins (IVIG), and plasmapheresis (PPH, 6x) (group RLP, n = 12 ). Between 2009 and June 2010, patients received bortezomib (1.3 mg/m 2, 4x) together with low-dose IVIG and PPH (group BLP, n = 11 ). In July 2010, we increased the IVIG dose and treated all subsequent patients with bortezomib, high-dose IVIG (1.5 g/kg), and PPH (group BHP, n = 11 ). Graft survival at three years after treatment was 73% in group BHP as compared to 45% in group BLP and 25% in group RLP. At six months after treatment median serum creatinine was 2.1 mg/dL, 2.9 mg/dL, and 4.2 mg/dL in groups BHP, BLP, and RLP, respectively (p = 0.02 ). Following treatment, a significant decrease of donor-specific HLA antibody (DSA) mean fluorescence intensity from 8467 ± 6876 to 5221 ± 4711 (p = 0.01 ) was observed in group BHP, but not in the other groups. Our results indicate that graft survival, graft function, and DSA levels could be improved along with stepwise modifications to our treatment regimen, that is, the introduction of bortezomib and high-dose IVIG treatment.